2002
DOI: 10.1034/j.1600-0501.2002.130302.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant osseointegration in the irradiated mandible

Abstract: This research focuses on the effects of radiotherapy on the osseointegration of dental implants placed before or after radiotherapy in 11 male beagles. After the extraction of all mandibular premolars 1st and 2nd molars, three dogs were implanted without radiotherapy (Control group), four dogs were irradiated 4 weeks after implantation (IrA group) and four dogs were irradiated 8 weeks before implantation (IrB group). Eight implants were placed in each dog, in an alternating pattern: four nonsubmerged ITI Bonef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
2
17
0
2
Order By: Relevance
“…Cortical bone remodelling was in progress several weeks after irradiation and appeared to follow its normal course, contrary to the findings in rabbits 18,24 . These observations therefore strengthen previous recommendations about radiotherapy planning 4,8,12 . In particular, the therapeutic timing and length of delay between irradiation and implantation appear decisive to ensure the correct osteogenic reaction and thus osseointegration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Cortical bone remodelling was in progress several weeks after irradiation and appeared to follow its normal course, contrary to the findings in rabbits 18,24 . These observations therefore strengthen previous recommendations about radiotherapy planning 4,8,12 . In particular, the therapeutic timing and length of delay between irradiation and implantation appear decisive to ensure the correct osteogenic reaction and thus osseointegration.…”
Section: Discussionsupporting
confidence: 87%
“…As described previously 7,8 , the clinical stability observed in all control implants, as well as in 61 of the 64 irradiated implants, clearly results from direct bone-implant contact, visible on the microradiographs of undecalcified sections (Fig. 3).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been suggested that a six-month period between irradiation and implantation should be implemented to allow improved bone apposition and adequate osseointegration (Brasseur et al, 2006). This finding is in line with data from Brogniez et al (2002), who reported progressive deposition of woven and lamellar bone around implants placed before or after irradiation of the bone, as well as a positive balance between bone resorption and remodeling after 8 weeks of radiotherapy. Histologic data on removed implants from irradiated human jaws suggest that bone anchorage of these implants is feasible (Bolind et al, 2006).…”
Section: Introductionsupporting
confidence: 79%
“…Trabecular bone has a porous structure and is located in medullary cavities (9,10). The effect of the implant parameters, bone quality and characteristic modulated by different aspects like aging, irradiation, tobaccoism, coffee consumption and alcohol consume, have been evaluated using several laboratory techniques (4,(10)(11)(12). From a macro-biomechanical perspective, the anchorage of implants has been assessed using tensile tests (13), torque (14), pull-out (2) and push-in tests (2).…”
Section: Introductionmentioning
confidence: 99%